Modelling one row of Horns Rev wind farm with the Actuator Line Model with coarse resolution. Issue 8 (September 2016) - Draper, M; Guggeri, A; Usera, G
Abstract: Actuator models have been used to represent the presence of wind turbines in a simulation in the past few years. The Actuator Line Model (ALM) has shown to reproduce with reasonable accuracy the wind flow through wind turbines under different operational conditions. Nevertheless, there are not many simulations of wind farms performed with the ALM mainly because of its computational cost. The aim of the present paper is to evaluate the ALM in spatial resolutions coarser than what is generally recommended, also using larger time steps, in a simulation of a real wind farm. To accomplish this, simulations of one row of Horns Rev wind farm are performed, for different wind directions. It is concluded that the ALM is able to capture the main features of the interaction between wind turbines relaxing its resolution requirements. A sensitivity analysis is performed to assess the influence of the smearing factor and the spatial resolution.